Historical Aspect of Gender Identification as Exemplified by Muslim Women in the Light of Tatar and Indian Background - Ferdinandovna Mratkhuzina, Guzel; Ilgizovna Khoraskina, Rezida; Vyacheslavovich Bobkov, Dmitriy; Gilkar Ahmad, Ishtiak (International Journal of Criminology and Sociology, 2022)
In the recent decades, investigation of transformation of gender relations in the countries of the world are becoming even more relevant. This process shows similar traits in societies of different type, yet in each country and in every region it takes a different path, which depends on a number of external and internal factors. It is interesting to compare the place and activity level of Muslim women in Tatarstan and India. Relevance of the investigated topic is attributed to the importance of understanding the ways and methods of awakening and development of the religious and national self-awareness of the Tatar people. As an essential tradition keeper of the Tatar people, Muslim women has long since functioned as enthusiastic defenders and supporters of restoration of religious and cultural traditions. Further relevance of the investigated topic is conditioned upon still debatable status of women in India, as they talk about equality of women in modern Indian society, while realities often prove to be different. The present article is aimed at achieving the following goal – exposing conceptual and factual content of the problems of Islam’s place in the system of religious identities of Tatar and Indian society, gender peculiarity of traditional Tatar and Indian society, status of Muslim women in Tatarstan and India and analysis of their social-political activity. The leading approach in investigating this topic is systemic and complex analysis and evaluation of the phenomenon of Indian Muslim women in the public perception and in the academic circles. The key findings of the article imply addressing the following research problems: 1) Scientifically-based reconstruction of the history of emergence and expansion of Islam in India; 2) Understanding of religious and gender peculiarity of Indian society; 3) Evaluation of historical limits, typology, scale and deepness of investigation of Muslim traditions in Indian society; 4) Justification of theoretical, historiographic, source-based foundation of the topic investigation, as well as systemization accumulated materials; 5) Determination of the degree of historical and culturological importance of the topic under consideration in Tatarstan. The materials of the article can be useful when determining relevant sectors of conventional and new agenda of the topic under consideration. Tatar and Indian women nowadays have achieved much, compared to Medieval times when their status in the society was utterly low. Yet in fact, they still have to go a long and difficult path to acquiring total freedom. Even though Indian women are still miles away from achievements of feminists in the West, yet due to social reformers the public is gradually beginning to recognize the true potential of women. As a result, old barriers started to break down, so Tatar and Indian Muslim women are gaining a rightful place in the society.